VALUASI EKONOMI EKOSISTEM LAHAN SAWAH DI DESA MONCOBALANG KECAMATAN BAROMBONG KABUPATEN GOWA - Anwar, Asriyani; Sribianti, Irma; Saleh, Syafiuddin (Fakultas Pertanian, Peternakan dan Perikanan Universitas Muhammadiyah Parepare, 2023)
This study aims to identify the economic benefits of paddy field ecosystems and analyze the value of the economic benefits of paddy field ecosystems in Moncobalang Village, Barombong District, Gowa Regency. The sampling method used a purposive technique, namely deliberately selecting respondents whose livelihoods were 83 farmers. Data was collected through interviews with respondents using a questionnaire. The method used to analyze the value of the economic benefits of the paddy field ecosystem uses an economic valuation method with a market price approach and the price of substitute goods. The calculated economic benefit value of the paddy field ecosystem is the direct benefit value, the indirect benefit value, the optional benefit value, and the existence benefit value. The results showed the economic benefit value of the paddy field ecosystem obtained, namely the direct benefit value consisting of the value of rice production and the production value of horticultural crops. The indirect benefit value was calculated from the value of agricultural waste products, as well as the optional benefit value calculated from the value of the paddy field ecosystem as a carbon sink and oxygen producer and the benefit value of the existence of paddy fields. The total value of the economic benefits of the paddy field ecosystem is IDR 8,813,171,208/ha/year, which consists of a direct benefit value of IDR 8,143,127,013/ha/year, the indirect benefit value is IDR 121,375,000/ha/year, the value of the optional benefits is IDR 416,369,190/ha/year, and the existence benefit value is IDR 132,300,000/ha/year.